Prevalence of cholelithiasis in patients with chagasic megaesophagus - Crema,Eduardo (2011)
INTRODUCTION: The prevalence of cholelithiasis in the general population ranges from 9 to 18%. This prevalence is known to be higher in the presence of parasympathetic nerve damage of the biliary tract either due to surgery (vagotomy) or neuronal destruction (Chagas disease). The objective of this study was to evaluate the association of cholelithiasis and chagasic or idiopathic megaesophagus. METHODS: The ultrasound scans of 152 patients with megaesophagus submitted to cardiomyotomy and subtotal esophagectomy surgery were evaluated. The presence of cholelithiasis was compared between chagasic and idiopathic esophagopathy and ultrasound and clinical findings were correlated with age, sex and race. RESULTS: A total of 152 cases of megaesophagus, including 137 with chagasic megaesophagus and 15 with idiopathic megaesophagus, were analyzed. The mean age was 56.7 years (45-67) in the 137 patients with chagasic megaesophagus and 35.6 years (27-44) in the 15 cases of idiopathic megaesophagus, with a significant difference between the two groups (p < 0.0001). The group with chagasic megaesophagus consisted of 59 (43%) women and 78 (56.9%) men, while the group with idiopathic megaesophagus consisted of 8 (53.3%) women and 7 (46.6%) men, showing no significant difference between the groups. Of the 137 patients with confirmed chagasic megaesophagus, 39 (28.4%) presented cholelithiasis versus one case (6.6%) in the 15 patients with idiopathic megaesophagus. CONCLUSIONS: The prevalence of cholelithiasis is high in patients with chagasic megaesophagus and preoperative ultrasound should be performed routinely in these patients in order to treat both conditions during the same surgical procedure.